Cerebral malaria is associated with low levels of circulating endothelial progenitor cells in African children - Gyan, B.; Goka, B.Q.; Adjei, G.O.; Tetteh, J.K.; Kusi, K.A.; Aikins, A.; Dodoo, D.; Lesser, M.L.; Sison, C.P.; Das, S.; Howard, M.E.; Milbank, E.; et al. (American Journal of Tropical Medicine and Hygiene, 2009)
Damage to the cerebral microvasculature is a feature of cerebral malaria. Circulating endothelial progenitor cells are needed for microvascular repair. Based on this knowledge, we hypothesized that the failure to mobilize sufficient circulating endothelial progenitor cells to the cerebral microvasculature is a pathophysiologic feature of cerebral malaria. To test this hypothesis, we compared peripheral blood levels of CD34 (+)/VEGFR2(+) and CD34 (+)/CD133(+) cells and plasma levels of the chemokine stromal cell-derived growth factor 1 (SDF-1) in 214 children in Accra, Ghana. Children with cerebral malaria had lower levels of CD34 (+)/VEGFR2(+) and CD34 (+)/CD133(+) cells compared with those with uncomplicated malaria, asymptomatic parasitemia, or healthy controls. SDF-1 levels were higher in children with acute malaria compared with healthy controls. Together, these results uncover a potentially novel role for endothelial progenitor cell mobilization in the pathophysiology of cerebral malaria.